Tracking the many meanings of activisms and occupations: an ethnographic study of ‘Reclaim the City’, in Woodstock and Green Point, Cape Town - Wingfield, Matthew Michael (Stellenbosch : Stellenbosch University, 2019)
Thesis (MA)--Stellenbosch University, 2019.